Complexity Simulation on Application of Asymmetric Bionic Cross-Section Rod in Pantographs of High-Speed Trains - Yan Cao; Yu Bai; Qiangfeng Wang (Complexity)
Ground transportation means and aircrafts with high-speed running are composed of many rod components. Aerodynamic noise generated therefrom is very outstanding. Reduction of the aerodynamic noise of rods becomes a hot topic in recent years. Most reported studies are tentative researches on aerodynamic noise of a pantograph or involve noise reduction of the pantograph with using porous materials or reshaping rod surfaces. Through using porous materials and reshaping rod surface, the aerodynamic noise of pantograph can be reduced to a certain extent, but the aerodynamic resistance will be increased and it is not convenient for practical application in engineering. Regarding this situation, the paper explores noise reduction performance of a feather on the back of a carrier pigeon and conducts the bionic design on rod surface. Through numerical simulation, the paper researches noise reduction performance of the bionic structure on the rod surface, reveals the mechanism of bionic noise reduction, and explores noise reduction effects of bionic structural rods on pantographs of the high-speed trains.